Students' knowledge, attitude and practices towards pressure ulcer prevention and management - Franco R. Abrahams; Edwin R. Daniels; Hileni N. Niikondo; Kristofina Amakali (AOSIS, 2023)
Background: Student nurses provide nursing care to patients during clinical allocation, and their competence may affect the quality of care given to the patients. Good knowledge and positive attitudes enhance early detection for prevention and management of pressure ulcers. Aim: To determine undergraduate nursing students' knowledge, attitude and practices (KAP) towards prevention and management of pressure ulcers. Setting: A nursing education institution in Windhoek, Namibia. Methods: A quantitative, cross-sectional research design was used to conveniently sample (n = 50) student nurses and collect data using a self-administered questionnaire. Data were analysed using the statistical software programme (SPSS) version 27. Descriptive frequencies were applied, and Fishers exact test was performed. A statistical value of p  0.05 was considered significant. Results: Fifty (n = 50) student nurses consented to participate in the study. Student nurses reported good levels of knowledge (n = 35; 70%), attitude (n = 39; 78%), practices (n = 47; 94%). There was no statistically significant association between demographic variables and the level of knowledge, attitudes and practices, p  0.05. Conclusion: Student nurses have good knowledge, positive attitudes and practices on prevention and management of pressure ulcers. By the implications, the study concludes that the nursing students will competently manage the pressure ulcers occurring in the clinical setting. An observational study is recommended to assess practices in the clinical setting. Contribution: The findings of this study will help to close the gap in the implementation of standard operating procedures for the prevention and management of pressure ulcers.